Studies on binary lipid matrix based solid lipid nanoparticles of repaglinide: In vitro and in vivo evaluation - Rawat M.K.; Jain A.; Singh S. (My University, 2025)
The purpose of present study is to examine effect of binary lipid matrix (combination of lipids) on the entrapment and storage stability of repaglinide (RG) loaded solid lipid nanoparticles (SLN). Solid lipid nanoparticles were prepared by modified solvent injection method for oral delivery to improve the bioavailability of RG, an antidiabetic drug. The stearic acid and tristearin were used to form lipid core materials, and Pluronic-F68 was used as a stabilizer. Nanoparticles were characterized by evaluating their particle size, zeta potential, entrapment efficiency, drug loading, solid-state studies (differential scanning calorimetry, X-ray diffraction), in vitro drug release, particle surface (transmission electron microscopy analysis with electron diffraction pattern), stability study in gastrointestinal fluids (GIFs) and storage stability at 30°C/65% RH for 3 months. The characterization of SLN suggested that binary lipid matrix based nanoparticles had better drug entrapment and loading, desired release characteristics, stable in GIFs and significantly higher storage stability compared with single lipid formulations. Pharmacodynamic (blood glucose, blood cholesterol, blood triglyceride levels) and pharmacokinetic (AUC, Tmax, peak plasma concentrations, K, t1/2, mean residence time and relative bioavailabilities) studies were performed for the selected formulations. These studies indicate that the formulation based on binary lipid matrix significantly improves the oral bioavailability of RG. © 2011 Wiley-Liss, Inc.